International context and local competitiveness. Smes and public services in the umbria region - Brocanello, Ilaria; Paoli, Massimo (Piccola Impresa / Small Business, 2013)
The ripple effects that the financial crisis triggered by the mid-2008 led to consequences for the real system. The correlation between the international markets has in fact facilitated the global spread of the negative effects of the financial crisis (Varaldo & Lamberti L., 2009). The aim of this paper is to analyse the operations of local Policy Maker (with special reference to ICE, National Institute for Foreign Trade) and the services offered in response to the current competitive environment, to support local SMEs (Barczyk, 2007; Wright, Westhead & Ucbasaran, 2007). The theoretical principles of strategic marketing for businesses, but also the institutions that provide services such as ICE, is based on a simple underlying principle: “... I do not offer what I produce, but I try to get and deliver the goods and services that customers / users want.” This principle implies and requires behavioural consequences, organizational, financial and operational business involving the entire organization to achieve an effective strategic marketing. The empirical investigation carried out by an activity started and promoted by ICE in Italy with the aim of facilitating the activitiesof penetration and consolidation of Italian companies in foreign markets according to different regional specificities. In this paper we present the activity in the region of Umbria. The survey was conducted with both qualitative and quantitative approach (Yin R.K., 2005). There have been 32 interviews and 150 questionnaires sent to SMEs in Umbria, with a redemption of 66.6%. The awareness of a necessary innovation in the range of services of the Institute, at the base of “The Listening Operation” promoted by ICE, is part of this strategic marketing and represents only the preparatory phase.